Productive performance, rumen parameters, carcass quality, antioxidant profile and methane emission in lambs supplemented with triticale hay - G.A. Izadi; Y. Rouzbehan; J. Rezaei; M.J. Abarghuei (Veterinary and Animal Science)
This study aims to measure the effects of different dietary concentrations of triticale hay (TH) on productive performance, carcass characteristics, microbial protein synthesis (MPS), ruminal and blood variables, and antioxidant power in 40 fattening male Gray Shirazi lambs (BW of 33.2 ± 1.1 kg) over 81 days in a completely randomized design (10 animals/diet). Four levels of TH (0.00, 13.30, 26.50, and 40.00 g/100 g dry matter; DM) were included in the diet, instead of alfalfa hay + barley straw. Dietary inclusion of TH decreased DM and nutrient intakes, but increased phenolic and flavonoid intakes, and digestibility of DM and nutrients (L, P < 0.01). Feeding TH did not affect daily gain, feed conversion ratio, carcass weight, dressing percentage, and Longissimus muscle area, decreased (L, P < 0.05) fat-tail, total carcass fat, and carcass stearic acid but increased (L, P < 0.05) lean-to-total carcass fat ratio, carcass oleic acid, polyunsaturated fatty acids (FA), and antioxidant power. Dietary TH increased ruminal MPS and cellulolytic bacteria but decreased ammonia-N, protozoa, and in vitro methane production (L, P < 0.01). Nitrogen retention and rumen short-chain FA were not affected by TH addition. Increasing dietary TH levels lowered (L, P < 0.01) blood cholesterol, triglyceride, and urea-N, but did not affect glucose, total protein, albumin, globulin, nitrate, and nitrite. Overall, TH can be included, up to 40 % of DM in the diet of fattening lambs, without effects on performance, to improve carcass quality, FA composition, and antioxidant capacity and reduce ruminal methane production.